If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(14x + 5) = 9x + 3 Reorder the terms: 0.5(5 + 14x) = 9x + 3 (5 * 0.5 + 14x * 0.5) = 9x + 3 (2.5 + 7x) = 9x + 3 Reorder the terms: 2.5 + 7x = 3 + 9x Solving 2.5 + 7x = 3 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 2.5 + 7x + -9x = 3 + 9x + -9x Combine like terms: 7x + -9x = -2x 2.5 + -2x = 3 + 9x + -9x Combine like terms: 9x + -9x = 0 2.5 + -2x = 3 + 0 2.5 + -2x = 3 Add '-2.5' to each side of the equation. 2.5 + -2.5 + -2x = 3 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + -2x = 3 + -2.5 -2x = 3 + -2.5 Combine like terms: 3 + -2.5 = 0.5 -2x = 0.5 Divide each side by '-2'. x = -0.25 Simplifying x = -0.25
| 3x+2y=37.50 | | 7+g=73 | | 4(y+3)+y=5Y+12 | | 2/5x-16 | | 4x-y^2=0 | | 4(5x-3)=-8x | | -3x+1=18 | | 25/35=Q10/k | | -5(1-3b)=10b+11(b-7) | | f(x)=x(x+3)-14 | | ln(4x/y3) | | 33=7(2p-1) | | 8n+7=2(4n+3) | | X/4-9/X=0 | | 7m^2-14m-61=-5 | | 5x=-7x+8 | | 1.8e=9 | | n+n+1+n+2=129 | | 2=0.6(2x+4)-0.75(4x-5) | | 2y+5=2(y+2)+1 | | 12k-15+15=54 | | -6x+3+3x=-7x-9 | | -y^2-y^2= | | -16x=33 | | 7m-3m-6=2m+12 | | 7/15÷3/4 | | 88-11=3x+9x-x | | 9z-4=2z+10 | | 8=x/-5 | | 7.25x=19.125+x | | 5m=6m+56 | | f(x+1)=8x^2+3x |